Excellence in public relations and communication management in Malaysia: an exploratory study / Associate Professor Dr Kiranjit Kaur - Kiranjit, Kaur (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2005)
This exploratory study examine s ho w head s o f public relation s department s manage public relations and communication to contribute to the effectiveness o f the organization; how CEOs and senior management explain the effectiveness o f an organization; and how employees view the contribution of public relations. Three different research instruments modified from those used in a previous similar research in USA and UK were used for this study.